Updated Czech guidelines for the laboratory diagnosis of Clostridium difficile infections - Krůtová, M; Nyč, O (Epidemiologie, mikrobiologie, imunologie, 2018)
Clostridium difficile, a causative agent of intestinal infections (CDI) of varying severity, is an important nosocomial pathogen. Microbiological diagnosis, including an appropriate test algorithm and the corresponding interpretation of the results, is crucial for CDI confirmation. This update is based on the European guidance document for CDI laboratory diagnosis, taking into account the current CDI epidemiology and laboratory diagnostic approaches in the Czech Republic. Any diarrhoeal patient should be tested for CDI. The rectal swabs can only be used for testing in patients with paralytic ileus. Currently, a two-step test algorithm is recommended for CDI diagnosis. Due to a low positive predictive value, a single commercial test is not recommended as a stand-alone test for diagnosing CDI. Samples with a positive screening test (glutamate dehydrogenase or toxigenic strain nucleic acid) and a subsequent negative EIA (enzyme immunoassay) test for the presence of free toxins are diagnostically inconclusive. An option is to use a third confirmatory test; however, the current clinical status of the patient along with other laboratory findings should be considered in order to differentiate between ongoing CDI, carriage of a toxigenic strain of C. difficile, and other causes of diarrhoea. In general, when implementing a new diagnostic test, its sensitivity and specificity should be compared against the reference method. Diagnostic tests should refer to the data from published comparative studies and should not rely solely on information provided by the manufacturer. Currently, there is no commercial test available for detection of free C. difficile toxins in stool samples with 100 % sensitivity. Moreover, the pre-analytical conditions (storage and transport temperature of stool samples) and/or the initiation of an empirical therapy prior to the sampling may decrease the sensitivity of the assay.
Keywords: Clinical Laboratory Techniques; Immunoenzyme Techniques; Feces; imunoenzymatické techniky; senzitivita a specificita; Sensitivity and Specificity; Clostridium difficile - laboratory diagnosis - laboratory testing algorithm - result interpretation.; klinické laboratorní techniky; bakteriální toxiny; Česká republika; feces; Humans; klostridiové infekce; lidé; Clostridium Infections; Bacterial Toxins; Clostridioides difficile; Czech Republic